Through the Looking Glass: Alice and the Constitutional Foundations of the Public Domain. - Benkler, Yochai (Law & Contemporary Problems)
Part of a special issue on the public domain. An examination of the general framework of the relationship between constitutional provisions in Article 1, Section 8, Clause 8 and the First Amendment and the power of Congress to regulate the use of information and cultural resources through exclusive private rights. The question of why it is appropriate to require close judicial scrutiny of congressional use of this particular form of regulation is discussed, and six specific pressure points on this framework are identified.